ENT 530 Social media portfolio: MG Perfume Your Scent / Ahmad Nur Hidayat Roslan - Roslan, Ahmad Nur Hidayat (2021)
MG Perfume is a perfume that has the content of natural ingredients using technology from Switzerland that can give a more enchanting, fresh and consistent fragrance effect from morning to night. MG Perfume has a well known scent that uses a Switzerland essence that won’t leave a yellow stain on any fabrics. it is very long lasting , easy to carry around and most importantly for muslims customers it is solat friendly